GLP in the European Union - Schmahl, Maik (Henry Stewart Talks, 2012)
Good Laboratory Practice, Definition and development, Differences and similarities to laboratory accreditation, The role of the EU Member States, the European Commission and the OECD, Cooperation with European agencies and regulatory authorities